(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Aim: The aim of the present study was to assess the knowledge, attitude and practice of recent diagnostic aids for oral cancer among dental students. Materials and Methods: This study was conducted among 100 students using a 15-item self-administered questionnaire during COVID-19 pandemic period involving both undergraduates and postgraduate dental students.It was formatted on google forms and shared through social media. The data collected was analysed statistically. Results: A total of 100 dental studentsparticipated in the survey. The total knowledge, attitude, and practice about recent diagnostic aids for oral cancer (based on summing all the positive responses – for all the relevant questions – and calculating the percentage) was 90% for post-graduates (highest), 88% for interns group, 84% for final years and 80% for third years (least) respectively.The results of this study show that postgraduates had good knowledge about recent diagnostic aids for oral cancer when compared to other groups. Conclusion: These findings concerning dental students suggests that they have sufficient knowledge in the recent diagnostic methods of oral canceras they are the ones who have higher chances of diagnosing oral cancer at earlier stages as they routinely examine oral cavity.